Use of red propolis in the treatment and prevention of oral mucositis in patients undergoing radiotherapy and/or chemotherapy: an integrative literature review (Research, Society and Development, 2022)
Objective: To evaluate the use of propolis in the prevention and/or treatment of oral mucositis (OM) induced by radiotherapy or chemotherapy in cancer patients. Methodology: This is an integrative review, using the databases Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO) and PubMed, published in English between 2011 and 2021. After searching the scientific literature, seven studies were selected for analysis of the therapeutic benefits of propolis in the prevention and/or treatment of chemotherapy and/or radiotherapy-induced OM. Results: The selected studies vary between Reviews, Meta-Analyses, double-blind randomized trials and phase two clinical studies. Most articles reported a positive effect of propolis in the treatment and/or prevention of recurrent oral aphthous ulcers and oral mucositis. Conclusion: The study concluded that propolis has been used as an intervention in clinical trials to observe its effectiveness in the prevention and/or treatment of oral mucositis in patients undergoing antineoplastic treatment, however, due to the lack of robust clinical data, there are no standardized and recognized protocols. by the Multinational Association of Supportive Care in Cancer (MASCC).